2014
DOI: 10.1007/s12010-014-0931-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Paraoxonase 1 (PON1) from Swiss Black, Holstein, and Montofon Bovines

Abstract: Paraoxonase 1 (PON1: EC 3.1.8.1) is a calcium-dependent enzyme associated with high-density lipoproteins (HDLs) and has a protective effect against oxidation of low-density lipoproteins (LDLs) in mammals. PON1 is the best-studied member of a family of enzymes called serum paraoxonases, or PONs, identified in mammals and other vertebrates as well as in invertebrates. PONs exhibit a range of important activities, including drug metabolism and detoxification of organophosphates such as nerve agents. This study re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Less than about 5% of PON1 activity for both substrates was found in very low density lipoprotein (VLDLs) and low density lipoprotein (LDLs) fractions. In the Holstein Friesian, Japanese Blacks, Swiss Blacks and Montofon bovine breeds PON1 was identified as 43 kDa protein (Miyamoto et al 2005, Erzengin et al 2014.…”
Section: Pon1 Synthesis and High Density Lipoprotein Associationmentioning
confidence: 99%
“…Less than about 5% of PON1 activity for both substrates was found in very low density lipoprotein (VLDLs) and low density lipoprotein (LDLs) fractions. In the Holstein Friesian, Japanese Blacks, Swiss Blacks and Montofon bovine breeds PON1 was identified as 43 kDa protein (Miyamoto et al 2005, Erzengin et al 2014.…”
Section: Pon1 Synthesis and High Density Lipoprotein Associationmentioning
confidence: 99%
“…This value is higher compared to Holstein race dry (97.17) and the postpartum period (83.17) average PON1 activities and as well as the peak lactation period's (90.93) determined by Kulka et al [22]. On the other hand, this value is lower compared to Holstein-Friesian (178.69), Polish Red (168.54) and Norwegian (145.8) race average values determined by Erzengin et al [14] and Kulka et al [23]. On the other hand, the average PON1 enzyme activity determined in this study (144.42) was similar to the average Holstein race value (152.29) determined by Turk et al [24], while it was lower compared to pregnant Holstein cows in first 3 months of pregnancy (283), 3 to 6 months of pregnancy (257), intramammary infusion (216) pre-puerperal in nonpregnancy (223), late puerperal (189), and peak lactation (329) values determined in the same study [24].…”
Section: Discussionmentioning
confidence: 72%
“…PON enzyme also has a certain degree of antioxidant activity [10,11]. It has been suggested that on cattle, factors like race, age, productivity period, and health issues can cause changes on PON1 enzyme activity [12,13,14].…”
mentioning
confidence: 99%
“…Some of these studies represented the starting point for the evaluation of cattle DME activities. However, it should be underlined that some enzyme-substrate kinetic studies have already been published for bovines [ 97 , 104 , 105 , 106 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%